ULAMA-ULAMA DAN TRADISI NASKAH DALAM TRANSFORMASI KEILMUAN FIQIH (HUKUM ISLAM) DI MINANGKABAU STUDI KASUS NASKAH-NASKAH FIQIH DI KABUPATEN AGAM - Doni Nofra; Inggria Kharisma (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2026)
The contribution of Ulama, congregation groups and their students of the intellectual traditions of the Minangkabau has been significant, manifesting in the form of impactful religious writings. This research project aims to analyse the process of transforming knowledge from these texts, both in the context of the teaching process and its transformation in the lives of the Minangkabau people. The text selected for analysis is that which addresses the theme of fiqih, which is distinctive and pertinent to the everyday concerns of the Minangkabau people. This research is qualitative in nature and employs historical research methods. The sources were obtained through observation, interviews and a review of the relevant literature. The data analysis process was conducted interactively from the outset of the research project. The findings of this research demonstrate that manuscripts originating from the Agam region present fiqih-related topics in a distinctive manner. The Minangkabau people are a diverse group with a range of socio-cultural backgrounds. The aforementioned themes encompass prayer, funeral arrangements, Hajj procedures, ablution, fasting, zakat, sacrifice, inheritance, qishash, trade, marriage, war and hunting. In addition, several other themes that are typically feminine are also addressed, including menstruation, women's fiqih, women's emancipation, and the interpretation of earthquakes. These texts are employed in surau settings and serve to advance social rights, particularly those pertaining to Minangkabau women in the domains of fiqih and social rights. The impact of scientific transformation is not limited to the continuity of religious education; it also has ramifications for social life.